The Use of Virtual and Augmented Reality in University Didactics in the Field of Logistics - Patrycja HOFFA-DABROWSKA (Communications of International Proceedings, 2024)
The development of information technology, including digitalization, affects the process of educating students. In order to ensure the best possible preparation of students to enter the labor market, it is necessary for educators to follow what is happening in business. There are many technologies available on the market. In this short article, I want to discuss the possibilities of using virtual and augmented reality in the didactic process of logisticians and share my own experiences in this area. The paper present using VR and AR application in the studies of Logistics – a real cases at University. The author presents at this article examples of benefits of using virtual reality and  augmented reality in combination with computer simulation in the logistics field.
Keywords: Virtual reality; augmented reality; university didactics; logistics.